Global rupture parameters for deep and intermediate-depth earthquakes (2016)
We investigate the global rupture parameters for deep and intermediate-depth earthquakes. From measurements of rupture duration and radiated seismic energy we estimate stress drop, apparent stress, and radiation efficiency and obtain a detailed earthquake energy budget. From scaling of the source parameters we highlight differences between crustal and deep seismicity, with the latter showing larger fracture energies. The observed increase of radiation efficiency with depth suggests that rupture mechanism for deep and intermediate-depth events differs. In agreement with previous studies we observe along-strike variability of rupture properties for deep and intermediate-depth earthquakes, correlating with slab morphology, plate age, or presence of volcanic structures. ©2016. American Geophysical Union. All Rights Reserved.